Testing the impact of quarterly results and analysts’ expectations on prices of selected equities - Šoltés, Viktor (Business, Management and Economics Engineering, 2012)
The aim of the article is to find the relationship between the growth and decline in the share price during the promulgation period of quarterly results of companies and surprise, either positive or negative in the quarterly results. Quarterly results are compared with the forecasts of analysts who publish their forecasts for quarterly results at Thomson Reuters and Bloomberg. Relationship is confirmed statistically, where stock returns in the period is the dependent variable, independent variables are three – return of the corresponding market index, excess impact – measure of surprise in quarterly results in comparison with analysts’ estimates and VIX index. Linear regression is used for testing of return and GARCH model is used for testing of volatility, there is focus on adaptation of actual volatility to the long-term average volatility after accidental shock.